2022
DOI: 10.24171/j.phrp.2022.0014
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of immunoglobulin G antibodies against SARS-CoV-2 in children and adolescents in Delhi, India, from January to October 2021: a repeated cross-sectional analysis

Abstract: Objectives: The aim of this study was to assess changes in the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) immunoglobulin G (IgG) seroprevalence among children and adolescents in Delhi, India from January 2021 to October 2021Methods: This was a repeated cross-sectional analysis of participants aged 5 to 17 years from 2 SARS-CoV-2 seroprevalence surveys conducted in Delhi, India during January 2021 and September to October 2021. Anti-SARS-CoV-2 IgG antibodies were detected by using the VITROS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Some of these show a lower seroprevalence from 0.23% to 14.4%, including 0.23% in Australia (November 2020 to March 2021), 10.8% in Germany (October to March 2021), 8.4% in Canada (March to April 2021) and 14.4% Belgium (September to October 2020) ( 18 21 ). Some of the studies have shown a higher seroprevalence such as 37% from Melbourne, Australia (May to October 2020), where the proportion in children was lower than that seen in adults (37% vs. 72%), 46.7% in Romania (March to June 2021), where it was seen to be similar to that in adults (45.6%) and increasing from 52.8% in January 2021 to 81.8% in September to October 2021 in Delhi, India ( 22 24 ). Since the vaccination among children was started later than adults, these studies were done prior to vaccination, however a direct comparison is not possible as they have been done around the world at different time points and relating differently to the waves of the pandemic in each country or continent except to understand that there are wide differences noted in seroprevalence, and some have shown a difference when compared to adults, while others have shown similar levels of seroprevalence.…”
Section: Discussionmentioning
confidence: 98%
“…Some of these show a lower seroprevalence from 0.23% to 14.4%, including 0.23% in Australia (November 2020 to March 2021), 10.8% in Germany (October to March 2021), 8.4% in Canada (March to April 2021) and 14.4% Belgium (September to October 2020) ( 18 21 ). Some of the studies have shown a higher seroprevalence such as 37% from Melbourne, Australia (May to October 2020), where the proportion in children was lower than that seen in adults (37% vs. 72%), 46.7% in Romania (March to June 2021), where it was seen to be similar to that in adults (45.6%) and increasing from 52.8% in January 2021 to 81.8% in September to October 2021 in Delhi, India ( 22 24 ). Since the vaccination among children was started later than adults, these studies were done prior to vaccination, however a direct comparison is not possible as they have been done around the world at different time points and relating differently to the waves of the pandemic in each country or continent except to understand that there are wide differences noted in seroprevalence, and some have shown a difference when compared to adults, while others have shown similar levels of seroprevalence.…”
Section: Discussionmentioning
confidence: 98%
“…[9] Another study was done among children and adolescents in Delhi in October 2021, which found 81.8% prevalence among the age group <18 years but no difference between urban and rural areas, male and female participants. [10] In the third round, almost in every category, the seroprevalence was high. However, among the vaccinated individuals still seroprevalence was higher.…”
Section: Discussionmentioning
confidence: 98%
“…In Manhiça district, a rural area located approximately 65 km from our study sites, a community survey with three cross-sectional periods reported, increasing seroprevalence of SARS-CoV-2 rates in participants younger than 20 years of age: 25.6% (April-June 2021), 58.2% (October-November 2021), and 82.6% (January-February 2022) [ 13 ]. The increase in the seroprevalence of anti-SARS-CoV-2 over time in children may be explained by the number of waves recorded by the country [ 9 11 , 24 ]. Mozambique reported, four waves between 2020 and 2022, which could increase children’s exposure over time as the number of infected young people increased within the waves [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased seroprevalence over time has been reported in different settings, primarily due to the emergence of variants of concern, which led to the reporting of different waves [ 9 11 ]. Mozambique reported four waves from June 2020 to January 2022 [ 12 ], and within that time, three cross-sectional studies in a rural area in the southern region of the country indicated that the seroprevalence increased from 25.6% (April-June 2021) to 58.2% (October-November 2021) and later to 82.6% (January-February 2022) in children and adolescents aged 0–19 years [ 13 ].…”
Section: Introductionmentioning
confidence: 99%